The process of making batik wayang beber using digital canting with sungging painting coloring technique - Aan Sudarwanto; Danang Priyanto (International Journal of Visual and Performing Arts, 2022)
This article carries the application of creating wayang beber patterns with sinjang batik techniques. This research aims to answer the endless question regarding the variation of batik patterns. Batik patterns are not only used in clothing but also as decoration. In this case, batik is used as decoration with wayang beber patterns using batik painting techniques. The research was carried out by making an example of a model, starting with looking for possible utilization by using a design from a computer graphics program. The research scope is limited by the creation of the wayang beber patterns and their application. The steps of designing are to create a prototype model, starting with conducting emic and ethical research. The next step is contemplating the whole pattern development design using digital technology. This is done by looking for suitability based on aesthetic principles and followed by pencantingan using the SGL-4332 series digital batik canting machine. For the final step, colouring is carried out using the batik painting technique, which is done manually using the rules of sungging gradation. This research produced a prototype model of wayang beber creation with batik techniques, which can be used by batik craftsmen to bring out new innovations in their work